Female Stroke: Sex Differences in Acute Treatment and Early Outcomes of Acute Ischemic Stroke. Issue 2 (February 2021) - Bonkhoff, Anna K.; Karch, André; Weber, Ralph; Wellmann, Jürgen; Berger, Klaus
Abstract : Background and Purpose: Men and women are differently affected by acute ischemic stroke (AIS) in many aspects. Prior studies on sex disparities were limited by moderate sample sizes, varying years of data acquisition, and inconsistent inclusions of covariates leading to controversial findings. We aimed to analyze sex differences in AIS severity, treatments, and early outcome and to systematically evaluate the effect of important covariates in a large German stroke registry. Methods: Analyses were based on the Stroke Registry of Northwestern Germany from 2000 to 2018. We focused on admission-stroke severity and disability, acute recanalization treatment, and early stroke outcomes. Potential sex divergences were investigated via odds ratio (OR) using logistic regression models. Covariates were introduced in 3 steps: (1) base models (age and admission year), (2) partially adjusted models (additionally corrected for acute stroke severity and recanalization treatment), (3) fully adjusted models (additionally adjusted for onset-to-admission time interval, prestroke functional status, comorbidities, and stroke cause). Models were separately fitted for the periods 2000 to 2009 and 2010 to 2018. Results: Data from 761 106 patients with AIS were included. In fully adjusted models, there were no sex differences with respect to treatment with intravenous thrombolysis (2000–2009: OR, 0.99 [95% CI, 0.94–1.03]; 2010–2018: OR, 1.0 [0.98–1.02]), but women were more likely to receive intraarterial therapy (2010–2018: OR, 1.12 [1.08–1.15]). Despite higher disability on admission (2000–2009: OR, 1.10 [1.07–1.13]; 2010–2018: OR, 1.09 [1.07–1.10]), female patients were more likely to be discharged with a favorable functional outcome (2003–2009: OR, 1.05 [1.02–1.09]; 2010–2018: OR, 1.05 [1.04–1.07]) and experienced lower in-hospital mortality (2000–2009: OR, 0.92 [0.86–0.97]; 2010–2018: OR, 0.91 [0.88–0.93]). Conclusions: Female patients with AIS have a higher chance of receiving intraarterial treatment that cannot be explained by clinical characteristics, such as age, premorbid disability, stroke severity, or cause. Women have a more favorable in-hospital recovery than men because their higher disability upon admission was followed by a lower in-hospital mortality and a higher likelihood of favorable functional outcome at discharge after adjustment for covariates. Abstract : Supplemental Digital Content is available in the text.